Three-sublattice order in the SU (3) Heisenberg model on the square and triangular lattice - Bauer, Bela; Corboz, Philippe; Läuchli, Andreas M; Messio, Laura; Penc, Karlo; Troyer, Matthias; Mila, Frédéric (Physical Review B, 2012)
We present a numerical study of the SU(3) Heisenberg model of three-flavor fermions on the triangular and square lattice by means of the density-matrix renormalization group (DMRG) and infinite projected entangledpair states (iPEPS). For the triangular lattice we confirm that the ground state has a three-sublattice order with a finite ordered moment which is compatible with the result from linear flavor wave theory (LFWT). The same type of order has recently been predicted also for the square lattice [PRL 105, 265301 (2010)] from LFWT and exact diagonalization. However, for this case the ordered moment cannot be computed based on LFWT due to divergent fluctuations. Our numerical study clearly supports this three-sublattice order, with an ordered moment of m = 0.2 − 0.4 in the thermodynamic limit.